2021
DOI: 10.4067/s0718-34292021000200067
|View full text |Cite
|
Sign up to set email alerts
|

Application of magnetically treated water during initial growth of bell pepper seedlings

Abstract: The cultivation of bell peppers, before transplanting, starts in nurseries to obtain uniform and vigorous seedlings. This study aimed to evaluate the effect of applying magnetically treated water on germination and the initial growth of bell pepper seedlings. Two experiments were conducted from August to October 2018 in a protected environment at the Irrigation Tecnic Center (CTI/ UEM) -Maringá, Paraná: the first in 50-cell polyethylene trays and the second in plastic containers (180 ml). Both experiments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Abedinpour and Rohani (2017) verified that maize seedlings that received magnetically treated water on an average germinated two days earlier than that of the control. The results presented by Lorenzoni et al (2021) showed that applying magnetically treated water to bell pepper seeds promoted its germination one day prior to those irrigated without magnetic treatment.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Abedinpour and Rohani (2017) verified that maize seedlings that received magnetically treated water on an average germinated two days earlier than that of the control. The results presented by Lorenzoni et al (2021) showed that applying magnetically treated water to bell pepper seeds promoted its germination one day prior to those irrigated without magnetic treatment.…”
Section: Resultsmentioning
confidence: 98%
“…The variable shoot fresh matter significantly differed for substrate 1 in experiment III, with a 63.65% increase when the seedlings received magnetically treated water. Few authors have verified that cultivating seedlings with magnetically treated water can maintain a higher gravimetric moisture and a lower evaporation rate (Álvaro et al 2019, Zolin Lorenzoni et al 2021.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation